2010
DOI: 10.1158/1078-0432.ccr-09-1380
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Polo-like Kinase in Cancer Therapy

Abstract: Polo-like kinases (Plk) function in mitosis and maintaining DNA integrity. There are four family members, of which Plk1 represents a target for anticancer therapy. Plk1 is only expressed in dividing cells with peak expression during G2/M. Plk1 functions in multiple steps of mitosis, and is overexpressed in many tumor types. Mitotic arrest and inhibition of proliferation, apoptosis, and tumor growth inhibition have been observed in preclinical studies using small interfering RNAs (siRNA) or small molecules that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
186
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(189 citation statements)
references
References 68 publications
3
186
0
Order By: Relevance
“…Therefore, Plk members are attractive drug targets for developing anticancer therapies and are the focus of several small-molecule screens (48)(49)(50). Unlike monomeric Plk1 which autoinhibits and requires multiple external inputs for its activity, Plk4 was not known to autoinhibit but instead was thought to rely on degradation (stimulated by trans-autophosphorylation) as its sole means of regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Plk members are attractive drug targets for developing anticancer therapies and are the focus of several small-molecule screens (48)(49)(50). Unlike monomeric Plk1 which autoinhibits and requires multiple external inputs for its activity, Plk4 was not known to autoinhibit but instead was thought to rely on degradation (stimulated by trans-autophosphorylation) as its sole means of regulation.…”
Section: Discussionmentioning
confidence: 99%
“…This mitotic kinase controls entry into and progression through mitosis at multiple stages by regulation of centrosome maturation, activation of initiating factors, degradation of inhibitory components, chromosome condensation, and exit from mitosis (reviewed in ref. 8). PLK1 is reported to be overexpressed in numerous cancers including melanoma, prostate, ovarian, colorectal, pancreatic, non-small cell lung, esophageal, endometrial, glioma, squamous cell carcinoma of the head and neck, and non-Hodgkins lymphoma (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…PLK1 is reported to be overexpressed in numerous cancers including melanoma, prostate, ovarian, colorectal, pancreatic, non-small cell lung, esophageal, endometrial, glioma, squamous cell carcinoma of the head and neck, and non-Hodgkins lymphoma (reviewed in ref. 8). Moreover, overexpression of PLK1 in DLBCL is linked to poor patient prognosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…Several RNA interference approaches targeting PLK1 have been investigated and gained certain success in kinds of tumor types. Numerous evidences indicated PLK1 expression level was down-regulated in many tumor types by RNA interference, for instance, breast cancer, stomach cancer, head and neck squamous cell carcinomas, colorectal cancer and a panel of other human cancers [31]. Series of previous studies also suggested knockdown of PLK1 by synthetic siRNA could inhibit cell proliferation, and promote the sensibility of breast cancer cells [15].…”
Section: Discussionmentioning
confidence: 99%